1982
DOI: 10.1021/np50023a026
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids of Garcinia kola Seeds

Abstract: Garcinia kola Heckel (Guttiferae), known in commerce as "bitter kola", is used extensively in African traditional medicine for the treatment of various diseases. In our investigations, the most common usage was found to be for the treatment of coughs and mouth infections. The plant is also used for the treatment of liver disorders. It is served in Nigerian homes to guests as an adjunct to the true kola nut. Garcinia species have been reported to be used BS an aphrodisiac (1) and for the treatment of diarrhea a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(80 citation statements)
references
References 1 publication
(1 reference statement)
3
71
0
Order By: Relevance
“…The seed of G. kola contains 1-3, 8-11 benzophenones, Garcinia biflavonones (GB-1, GB-2) and kolaflavonone (Cotterih et al, 1978). Apigenin based flavonoids represent 60% of the total flavonoids present in the diethyl ether fraction of G. kola seeds (Iwu and Igboko, 1982). The seed of G. kola has similarly been used to prevent and treat colic and headache (Ayensu, 1978), jaundice, high fever and liver disorders (Iwu, 1991), skin infections, sexual dysfunction and stomach pain (Braid, 1991) and as a spermatogenic agent (Adesanya et al, 2007).…”
Section: Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…The seed of G. kola contains 1-3, 8-11 benzophenones, Garcinia biflavonones (GB-1, GB-2) and kolaflavonone (Cotterih et al, 1978). Apigenin based flavonoids represent 60% of the total flavonoids present in the diethyl ether fraction of G. kola seeds (Iwu and Igboko, 1982). The seed of G. kola has similarly been used to prevent and treat colic and headache (Ayensu, 1978), jaundice, high fever and liver disorders (Iwu, 1991), skin infections, sexual dysfunction and stomach pain (Braid, 1991) and as a spermatogenic agent (Adesanya et al, 2007).…”
Section: Histologymentioning
confidence: 99%
“…Its alkaloid and bioflavonoids content are said to relax muscles (Braid, 1989). G. kola stem bark contains a complex mixture of phenolic compounds such as bioflavonoid, xanthones and benzophenone (Iwu and Igboko, 1982) as well as several organic compounds which confer on it some antimicrobial and antifungal properties (Bohn, 1968). Garcinia kola is found in rain forest and swamps and grows to about 12m in height.…”
Section: Introductionmentioning
confidence: 99%
“…Several heterocyclic compounds have been isolated from this source (Iwu and Igboko, 1982;Kabangu et al, 1987;Terashima et al, 1999) including -tocotrienoloic acid 5, which is also known as garcinoic acid (Delle Monache et al, 1984;Terashima et al, 1997;Terashima et al, 2002;Mazzini et al, 2009). Apart from its antioxidant (Terashima et al, 1997;Terashima et al, 2002) and DNA polymerase inhibition (Maloney and Hecht, 2005), numerous, mainly anecdotal, effects resulting from the ingestion of these nuts are appreciated by people using them (Adebisi and Song, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In Ivory Coast, the leaves are taken as a decoction to relieve tooth pain (Visser, 1975). Previous phytochemical studies indicated that mostly xanthones (Kuete et al, 2007a), benzophenones (Ahmad et al, 2010), triterpenes (Chung et al, 1998), flavonoids, and biflavonoids (Iwu & Igboko, 1982) were found in the genus Garcinia and they exhibited antioxidant, antimicrobial, antiinflammatory, and antitumor activities (Hay et al, 2004).…”
Section: Introductionmentioning
confidence: 99%